1991
DOI: 10.1097/00006842-199111000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and coronary heart disease: potential psychophysiologic mechanisms.

Abstract: Although there has been extensive research attempting to identify psychophysiologic mechanisms linking psychological events and behavior patterns with risk for coronary heart disease, these are important potential mechanisms that remain largely unexplored. One of these mechanisms is thrombosis, which is widely recognized as the precipitant of acute coronary events (myocardial infarction and sudden ischemic death). A major element in arterial thrombosis is the platelet, and platelet inhibition has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(90 citation statements)
references
References 133 publications
0
88
0
2
Order By: Relevance
“…They have α-2, β-2 adrenoceptors, benzodiazepine and 5-HT (1, 2, 6, 3) receptors on their membranes [19]. Markovitz et al [20] found that emotional stress increases platelet activity and suggested that stressors may play an important role in vascular events such as myocardial infarction. In the case of increased stress and anxiety, serotonin binds to 5-HT-2 receptors on platelets and mediates the release of factors that promote platelet aggregation [21].…”
Section: Discussionmentioning
confidence: 99%
“…They have α-2, β-2 adrenoceptors, benzodiazepine and 5-HT (1, 2, 6, 3) receptors on their membranes [19]. Markovitz et al [20] found that emotional stress increases platelet activity and suggested that stressors may play an important role in vascular events such as myocardial infarction. In the case of increased stress and anxiety, serotonin binds to 5-HT-2 receptors on platelets and mediates the release of factors that promote platelet aggregation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Markovitz & Matthews (133) initially proposed that enhanced platelet response to psychological stress is a key mechanism whereby psychosocial stress may trigger acute ischemic events and contribute to the development and progression of CVD. Figure 1 is an adaptation and extension of their proposed model, which incorporates additional mechanisms discussed in this review.…”
Section: Platelet Activationmentioning
confidence: 99%
“…Anger expression has been positively correlated with platelet aggregability (219). The relation between psychosocial factors and platelet activation and/or reactivity may be mediated, at least in part, by alterations in serotonergic function (133).…”
Section: Platelet Activationmentioning
confidence: 99%
“…Increased platelet reactivity is another hypothesis proposed by Markovitz and Matthews (1991) that could account for increased cardiovascular risk from psychological stress. During a stress response, lipids are released and deposited in the cardiovascular system.…”
Section: Stress Reactivitymentioning
confidence: 99%
“…During a stress response, lipids are released and deposited in the cardiovascular system. Stress causes activation of blood platelets that responds to and activates the clotting cascade (Markovitz & Matthews, 1991). Repeated or prolonged stress responses lead to a buildup of plaque and eventual thrombosis, heart failure, and possible myocardial infarction.…”
Section: Stress Reactivitymentioning
confidence: 99%